2019
DOI: 10.1002/nla.2228
|View full text |Cite
|
Sign up to set email alerts
|

On the distribution of real eigenvalues in linear viscoelastic oscillators

Abstract: Summary In this paper, a linear viscoelastic system is considered where the viscoelastic force depends on the past history of motion via a convolution integral over an exponentially decaying kernel function. The free‐motion equation of this nonviscous system yields a nonlinear eigenvalue problem that has a certain number of real eigenvalues corresponding to the nonoscillatory nature. The quality of the current numerical methods for deriving those eigenvalues is directly related to damping properties of the vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
(73 reference statements)
0
4
0
Order By: Relevance
“…Therefore, the reader must be aware that nonviscous modes without an oscillatory nature will be present always in nonviscously damped structures based on kernels with exponential decay, no matter the damping level. Some works specifically devoted to the study of nonviscous modes can be found in the references [8,[20][21][22], where, in particular, Mohammadi and Voss propose a mathematical characterization [20] and study their distribution [21]. However, in the context of the current investigation, overdamped modes are those whose non-oscillatory nature (as negative real numbers) can be affected by the damping level, so that they can be transformed into complex underdamped modes with oscillatory natures for low damping conditions.…”
Section: New Results On Critical Damping Of Structures With Viscoelas...mentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, the reader must be aware that nonviscous modes without an oscillatory nature will be present always in nonviscously damped structures based on kernels with exponential decay, no matter the damping level. Some works specifically devoted to the study of nonviscous modes can be found in the references [8,[20][21][22], where, in particular, Mohammadi and Voss propose a mathematical characterization [20] and study their distribution [21]. However, in the context of the current investigation, overdamped modes are those whose non-oscillatory nature (as negative real numbers) can be affected by the damping level, so that they can be transformed into complex underdamped modes with oscillatory natures for low damping conditions.…”
Section: New Results On Critical Damping Of Structures With Viscoelas...mentioning
confidence: 97%
“…Remember that each point of the curves is associated to a real eigenvalue of the form s = −ω j /α, and this does not exclude the so-called nonviscous modes, also presented in the problem D(s)u = 0. These nonviscous eigenvalues become more relevant as the viscoelasticity increases [8,21], although they are not properly classified as overcritical; consequently they may lay outside the overdamped region as, indeed, it occurs (see Figure 2d). Therefore, the presence of non-viscous eigenvalues somehow makes the identification of critical regions more difficult.…”
Section: Critical Curves Between C 1 and C 2 (Type I)mentioning
confidence: 99%
“…(2). Thus, eigenvalues of lightly damped systems will be formed by a conjugate-complex pair (with oscillatory nature) and N negative-real numbers called nonviscous eigenvalues [4,5,6] (these latter without oscillatory nature). Meanwhile, high damping can lead to a completely overdamped system in which all the 2 + N eigenvalues are negative-real numbers.…”
Section: Introductionmentioning
confidence: 99%
“…The oscillatory nature of the roots (or eigenvalues) depends mainly on the mathematical form of the damping function in the frequency domain, which in turn is governed by several damping parameters along with its dependence on s. The level of dissipation induced in the system is somehow controlled by these parameters because the eigenvalues implicitly depend on them through the relationship established in equation (2). Thus, eigenvalues of lightly damped systems will be formed by a conjugate-complex pair (with oscillatory nature) and N negative-real numbers called nonviscous eigenvalues [4][5][6] (these latter without oscillatory nature). Meanwhile, high damping can lead to a completely overdamped system in which all the 2 + N eigenvalues are negative-real numbers.…”
Section: Introductionmentioning
confidence: 99%